2020
DOI: 10.4047/jap.2020.12.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate and clinical evaluation of the implants in implant assisted removable partial dentures: surveyed crown and overdenture

Abstract: PURPOSE. The purpose of this study was to investigate survival rates of the implants used in implant assisted removable partial dentures (IARPDs). MATERIALS AND METHODS. The study was conducted on 21 patients who were treated with IARPDs. The mean follow-up period for IARPD patients ranged from 12 to 185 months (mean 47.9 months). A total of 58 implants were used for IARPDs in two different modalities: 41 for surveyed crowns and 17 for overdentures. The survival of implants was determined by clinical and radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 40 publications
1
30
1
Order By: Relevance
“…A previous study showed when the opposing dentitions were RPD or CD, there were no implant failures, resulting in a 100% survival rate [ 47 ]. In the present study, all opposing dentitions were natural teeth, fixed implant prostheses, or IOD, and overall implant survival rate was 84.1%.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed when the opposing dentitions were RPD or CD, there were no implant failures, resulting in a 100% survival rate [ 47 ]. In the present study, all opposing dentitions were natural teeth, fixed implant prostheses, or IOD, and overall implant survival rate was 84.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Usually survival rates for fixed implants in edentulous patients are reported in the range of 92.1% [ 22 ] to 95.6% [ 23 ]. Kang et al showed that the survival rate of implants in IC-RPDs for partially edentulous mandible was 93.1% [ 24 ]. The 5-year prospective randomized study by Gotfredsen and Holm showed a success rate of 100% in IODs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…IARPD or ISRPD can overcome the shortcomings of distal extension RPDs less invasively and more economically [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. An ISRPD in which implants provide support only, not retention, can be a simple method [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ] and can avoid subsequent complications [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients are note able to have a sufficient number of implants because of conditions such as residual bone volume and quality. To overcome these problems, the use of implants as source of support and retention for distal extension RPD was introduced and has since been evaluated [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. This type of prosthesis is generally called “implant-assisted RPD (IARPD)” [ 5 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation